Sosialisasi Pencegahan Penyakit Tidak Menular dengan CERDIK pada Lansia di Posyandu Kemuning RT 01 RW 08 Desa Made - Annisa' Carina; Luqman Cahyono; Ratna Fajarwati Meditama (Jurnal Empathy Pengabdian Kepada Masyarakat, 2025)
Background: Non-Communicable Diseases (NCDs) are one of the main health challenges in Indonesia, especially for the elderly. To reduce the risk of NCDs, prevention efforts are needed through education and implementing a healthy lifestyle. The CERDIK program (regular health checks, get rid of cigarette smoke, be diligent in physical activity, have a healthy and balanced diet, get enough rest, manage stress) is an effective approach in supporting the prevention of NCDs. This outreach activity was carried out at Posyandu Kemuning RT 01 RW 08 Made Village with the aim of increasing the understanding and awareness of the elderly regarding the prevention of NCDs. Methods: This activity included interactive education, practical simulations, group discussions, and simple health checks. The activity was attended by the elderly from RT 01 RW 08 and involved posyandu cadres and village midwives. The community service activities were carried out in four stages, namely preparation, implementation of socialisation, mentoring and evaluation, and follow-up. Results: This activity showed an increase in participant knowledge, participant understanding in doing simple physical activities, and understanding of the importance of healthy eating and exercising. The mentoring and education program provided showed an average increase in scores of 42.4% in three main aspects: knowledge, understanding of physical activity, and motivation for healthy living. Conclusion: This activity emphasizes the importance of a community-based approach to support the sustainability of a healthy lifestyle. With ongoing mentoring and education, it is hoped that this program can have a long-term impact in reducing the prevalence of NCDs in the elderly.